KAJIAN KUALITAS FISIK KIMIA DAN BIOLOGIS KAWASAN PERAIRAN DANAU BATUR DI PROVINSI BALI - , DEWA AYU TISMAYUNI, Dr. Erny Poedjirahajoe, M.P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Lake Batur is the largest lake in the province of Bali. The surrounding area of lake Batur is significant for agricultural, fisheries and tourism activities. Those activities may affect negatively on the ecological and aesthetic functions of the ecosystem of Lake Batur. This study aims to identify the physic, chemical, and biological water qualities of Lake Batur areal to determine the water quality level using STORET method. This study was conducted in March 2013 by collecting primary data and secondary data in 2011 and 2012 on physico-chemical and biological quality of Lake Batur area. The measurement of physical water quality parameters includes water temperature and Total Dissolved Solid (TDS). The chemical quality parameters measured were water pH, dissolved oxygen level, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), phosphate consentration, and ammoniac consentration. The water quality biological parameter of total coliform level in the water was measured. STORET analyses on the water quality of Lake Batur is categories as polluted. There are some water parameters that are above the standard quality required, such as water pH, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and phosphate consentration. This may be caused by activities surrounding the Lake Batur, such as agricultural, fisheries, housing and tourism activities